Newton’s Laws, G-forces and the Impact on the Brain - Vicki Evans (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
The thrill to go fast and push boundaries is something that many seek. From John Stapp’s rocket sled at Edwards Air Force Base in the late 1950’s to todays’ Formula 1 drivers, the “need for speed” is broadcast across TV screens weekly. So too are the horror stories of crashes, many at over 300 km/hr. Yet “need for speed” continues. It appears that the higher and faster the rollercoaster, the better. This leads to several questions. How does the brain stand up to speed and G-forces? Do Newton’s Laws still have reference in today’s world? There has been much attention in the general press on the possibility that high G-force roller-coasters are inducing brain injury in riders. However, research does not wholeheartedly support this notion, but rather the risk of brain injury from a rollercoaster is not in the rides, but in the rider — caused by previously undetected brain or neck conditions. That said there is some truth that high G-forces do affect the brain at a chemical and structural level. This paper will discuss the mechanism of head injury at speed and generally what Newton’s Law means in a neurological setting in todays’ world. Formula 1 racing and rollercoaster rides will be evaluated within a neuroscience context. (JNNN 2019;8(3):133–137)